Pengaruh Penerapan Model Problem Based Learning (PBL) Terhadap Kemampuan Pemecahan Masalah Siswa Sekolah Dasar Pada Pembelajaran Matematika - Puja Widya Ningrum; Fitri Nuraeni; Jennyta Caturiasari (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This research is motivated by the low problem-solving ability of students caused by the use of the learning model used by the teacher which is dominated by lectures and memorizing formulas. The Problem Based Learning (PBL) model is expected to be a solution to these problems. The purpose of this research is to find out whether there is an increase in problem-solving skills that get a better Problem Based Learning (PBL) model than students who get conventional learning, and to find out whether there is an effect of the Problem Based Learning (PBL) model on problem-solving abilities. This research is a quasi-experimental type of research with a non-equivalent control group design. The sample in this study were students of class Va and Vb at a public elementary school in Purwakarta. The research instrument used is in the form of description and documentation questions. Problem solving ability test instrument to obtain pretest and posttest quantitative data of students. Based on the research results obtained, it shows that: 1) The improvement of the problem solving abilities of elementary school students who receive the Problem Based Learning (PBL) model is better than students who receive conventional learning; 2) There is an effect of applying the Problem Based Learning (PBL) model to increasing the problem solving abilities of elementary school students. Thus the Problem Based Learning (PBL) model is recommended by the author as an alternative learning to improve problem solving skills. Keywords: Problem Based Learning (PBL) Approach; Problem Solving Ability; Mathematics Learning.